Approaches to the Direct Contracting Regime in the New Public Procurement Law Regarding the Draft Regulation of Law No. 30225, whose publication was provided by Ministerial Resolution No. 216-2015-EF / 15 - Pedreschi Garcés, Willy (2015)
The present article treats about the main innovations brought on the direct contracting regimen of the Public Procurement Peruvian New Law. In the author’s opinion, the new law seeks to make public procurement more efficient. Thus, he explains us how, in direct contracting, the law tries to achieve this objective.In that line, the paper explains the cases in which the direct contract proceeds and the formalities and requirements for it.